Human immunodeficiency virus reverse transcriptase. Substrate and inhibitor kinetics with thymidine 5'-triphosphate and 3'-azido-3'-deoxythymidine 5'-triphosphate - Reardon, J E; Miller, W H (The Journal of biological chemistry, 1990)
3'-Azido-3'-deoxythymidine 5'-triphosphate (AZTTP) was an efficient substrate for the human immunodeficiency virus 1 reverse transcriptase. It was incorporated into both homopolymer and defined sequence DNA-primed RNA templates and DNA-primed DNA templates. The substrate and inhibitor kinetics of both AZTTP and dTTP were dependent on the template-primer and reaction conditions used. dTMP was incorporated into poly(rA).oligo(dT) and into a defined sequence DNA-primed RNA template (when the other three 2'-deoxynucleoside 5'-triphosphates were present) as a conventional substrate, with steady-state Km values of 5-10 microM. The results suggest that the reverse transcriptase was capable of processive DNA polymerization on these DNA-primed RNA templates. In contrast, in the absence of the other three 2'-deoxynucleoside 5'-triphosphates, the time course for incorporation of dTMP into the same defined sequence DNA-primed RNA template was biphasic. A burst of product formation was observed followed by a slow steady-state rate with a Km value of 0.082 microM. AZTMP incorporation into poly(rA).oligo(dT) and into the defined sequence DNA-primed RNA template produced similar biphasic time courses and steady-state Km values. These results were consistent with rate-limiting dissociation of the polymerase.template-primer complex after "forced" termination of polymerization. AZTMP and dTMP were both incorporated into the homopolymer DNA-primed DNA template, poly(dA).oligo(dT), and a defined sequence DNA-primed DNA template as conventional substrates. Their Km values were similar (2-10 microM). The absence of biphasic time courses suggested that dissociation of the DNA-primed DNA templates from the enzyme, after forced termination, was not rate-limiting. This was consistent with a more distributive mode of DNA polymerization. With the defined sequence template-primers and poly(dA).oligo(dT), Ki values for both dTTP and AZTTP were comparable to their Km values. Thus, AZTTP appeared to be a simple competitive substrate-inhibitor with respect to dTTP. AZTTP inhibition of dTMP incorporation into poly(rA).oligo(dT) was linear competitive at low concentrations (0-100 nM) of AZTTP (Ki = 35 nM) but became hyperbolic (decreasing potency) at concentrations of AZTTP above this range. A mechanism for this nonlinear inhibition is discussed.